Pelaksanaan Pelayanan Gawat Darurat Bagi Peserta Bpjs Kesehatan Di Rumah Sakit Umum Daerah Ratu Aji Putri Botung Ditinjau Dari Keputusan Menteri Kesehatan Nomor 856/Menkes/Sk/Ix/2009 Tentang Standar Instalasi Gawat Darurat (IGD) Rumah Sakit - Jansje Grace Makisurat; Y. Budi Sarwo; Daniel Budi Wibowo (SOEPRA, 2018)
Indonesian Hospital is a health service facility to support the implementation of health efforts. RSUD in collaboration with BPJS often accepts patients not according to the criteria of emergency criteria. This study aims to determine the implementation of emergency services for participants JKN Health in IGD and Decree of the Minister of Health of the Republic of Indonesia No. 856 / Menkes / SK / IX / 2009 on Emergency Installation Standards.This research was conducted at the General Hospital of Ratu Aji Putri Botung Area. This research uses sociological juridical approach method with analytical descriptive specification. The data used are primary and secondary data through observation and interview 60 respondents to Head of Health Service, Head of Medical Service, Head of Room of IGD, Head of Unit of Integrated Health Insurance, and manager of BPJS. Data of research result is analyzed by using qualitative method.The results showed that JKN participants were aware of the service flow (32%), were aware of referral service flow (20%), were aware of the emergency’s criteria (28%) and were aware of the JKN participants' rights and obligations (48%). It is because lack of understanding on JKN regulation that become obstacle to access IGD services. Patients who have applied service at the Regional Public Hospital’s emergency unit were served according to the service flow regulated by BPJS. The Triage method was conducted to patients who applied for service at the Emergency unit to sort out which are emergency cases and which are not. RSUD RAPB has not implemented KMK Number 856 / Menkes / SK / IX / 2009 on Hospital's Emergency Unit Standard  was not properly implemented in the hospital includes the absence of legal sanction and the absence of a clear regulation at the regional level, therefore the legalization and modification the regulation is required for the legal product to be effective. Budget support from the government and local government is needed for optimal health service delivery in RSUD RAPB. Supervision and guidance from the Department of Health is needed as a control in ensuring that the regulations are being properly implemented. Intensive socialization by BPJS is required in order to make changes in the general community behavior so that people would understand and obey the rules as JKN participants.